IMPLEMENTASI METODE EXPERIENCE LEARNING SEBAGAI UPAYA PENINGKATAN KOMPETENSI PEMBELAJARAN MATAKULIAH PERILAKU ORGANISASI - Aniek Rumijati (Universitas muhammadiyah malang, 2011)
Fakultas Ekonomi Universitas Muhammadiyah MalangE-mail : rumijati@umm.ac.idABSTRACTThis study aims to enhance knowledge, skills and attitude of students in learning.OrganizationalBehavior course. It is also an effort to increase student involvement in the learning process. Byapplying Learning Experience Method which place more emphasis on experience, students are ableto feel, express and enhance personal development (soft skills). The method used was to compare theexperience between the use of constructivist learning is a method in an experimental class usinglecture and discussion on the control class.Observations on the experimental class and control class obtained results indicate that the methodis considered more interesting learning experience and fun, the involvement of students in the learningprocess more student skills can be improved and enhanced. In addition, if viewed from the aspect ofstudent satisfaction attitudes towards learning experience methods showed higher yields than lecturemethod and discussion. Another indicator used is the value of midterm test and final test as anindication of the cognitive aspect or understanding of students in the experimental class obtainedbetter results than the control class. The implication of this study found that use of the method oflearning experience in Organizational Behavior course better than the lecture method anddiscussionKeywords: experience, learning, constructivist, lectures and discussions